Prevalence of oral lesions in Brazilian patients with tuberculosis - Rodolfo Albuquerque Santiago; Luiz Alcino Gueiros; Stephen Ross Porter; Valder Barbosa Gomes; Iracema Ferrer; Jair Carneiro Leão (Wolters Kluwer Medknow Publications, 2013)
Background : Oral lesions of tuberculosis (TB) are rare and usually associated with the secondary form of the disease. Aim : The aim of the present study was to determine the prevalence of oral lesions in a cohort of TB-infected individuals. Materials and Methods : The study was carried out in two reference centers for the treatment of TB in Recife, Brazil. All patients treated for TB in the period from July 2008 to March 2009 were included in the study. The data was subjected to descriptive statistical analysis. Results : One hundred and twenty-one patients were included in the study. A marked male prevalence was observed, with a male:female ratio of 6.12:1. HIV coinfection was a common event (33%). Head and neck lesions of TB were rare. Cervical node enlargement was observed in seven individuals (5.8%) and oral ulceration in one patient (0.8%). Discussion : The low prevalence of oral lesions of TB is in accordance with other studies. Nodal involvement is the most common form of head and neck disease. Conclusion : While TB may be a common accompanying feature of HIV disease, orofacial complications of TB are rare in individuals resident in northern Brazil.